Meningkatkan Aktivitas dan Hasil Belajar Menggunakan Teknologi Model Pembelajaran Index Card Match - Helda Mulyani (Universitas Islam Negeri Imam Bonjol Padang, 2010)
The education system should also foster a patriotic spirit, strengthen love for the fatherland, enhance the spirit of nationalism and social fiendship, and ready to appreciate the services of pre hero and willing to go forward. Teaching and learning climate that can foster self-confidence and learning culture in the society continue to be developed in order to grow the attitudes and behaviors kreative, innovative and oriented towards the future. More assertive in the Act on National Education System No.20 of 2003 regulates the education in Unit, Educational Level, Educational Path, type of education. Implementation Model Index Card Match Pembelajran in learning Citizenship Education has been able to increase the activity and student learning outcomes. In the first cycle in the process learning have seen increased activity following the students' learning readiness of students who bring textbook, students who took notes, and students who bring stationery. Likewise, students in the learning activity that copied of learning goals, students are asking questions, students who gave feedback/ answers to questions, students who actively discuss, students who make the task, and students who make the conclusion there was an increase.